2005
DOI: 10.1002/ijc.20872
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 semiquantitative viral load and serologic biomarkers in oral and oropharyngeal squamous cell carcinomas

Abstract: A considerable subset of oropharyngeal squamous cell carcinomas (SCCs) are positive for human papillomavirus (HPV); however, delineating etiologically-associated HPV infections from SCCs with concurrent HPV infection unrelated to tumorigenesis is challenging. Viral load assessment in biopsy specimens may help facilitate such differentiation. HPV16 viral load and serologic markers were assessed among oral and oropharyngeal cases from a multinational study conducted by the International Agency for Research on Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Previous studies have confirmed, however, that detection of antibodies against E6 and E7 oncoproteins shows good correlation with HPV DNA in the tumour tissue 32. Kreimer et al .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have confirmed, however, that detection of antibodies against E6 and E7 oncoproteins shows good correlation with HPV DNA in the tumour tissue 32. Kreimer et al .…”
Section: Discussionmentioning
confidence: 93%
“…There is escalating evidence of a causal association between HPV and OSCC, [82][83][84][85][86][87][88][89][90][91][92][93] with several studies showing that HPV is associated with increased risk of oral cancer, independently of exposure to tobacco and alcohol. 84,86,88,89 This association is valid for high-risk HPV, which comprises subtypes 16, 18, 33, and 35.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
“…HPV-16 may be responsible for more than 80% of HPV-positive OSCC. 82,83,[85][86][87][88]90,93 The virus can be detected in tissues or cells using several methods, namely, biochemical, immunologic, microscopic, and molecular. Polymerase chain reaction is considered the most sensitive assay.…”
Section: Review Of the Literature Patient-related Factorsmentioning
confidence: 99%
“…In all cultures, both CD8þ and CD4þ T cells grew out (CD4/CD8 ratio median 2.45, average 5.1 and range 0. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The composition of T cells was not clearly influenced by the culture conditions (Fig.…”
Section: Hpv-specific T Cells Can Be Isolated From Oropharyngeal Tumomentioning
confidence: 99%
“…8 In addition, circulating antibodies to HPV16 have been detected in HNCSCC patients with high viral load and it is suggested that the HPV-specific antibody status is related to clinical outcome. 9,10 In nonviral-induced, smoking and drinking-associated HNCSCC, p53 overexpression is one of the most common abnormalities identified. Mutation of p53 is correlated with poor prognosis.…”
mentioning
confidence: 99%